Kinetic Analysis of Membrane Potential Dye Response to NaV1.7 Channel Activation Identifies Antagonists with Pharmacological Selectivity against NaV1.5. (June 2016) - Finley, Michael; Cassaday, Jason; Kreamer, Tony; Li, Xinnian; Solly, Kelli; O'Donnell, Greg; Clements, Michelle; Converso, Antonella; Cook, Sean; Daley, Chris; Kraus, Richard; Lai, Ming-Tain; et al.
The NaV 1.7 voltage-gated sodium channel is a highly valued target for the treatment of neuropathic pain due to its expression in pain-sensing neurons and human genetic mutations in the gene encoding NaV 1.7, resulting in either loss-of-function (e.g., congenital analgesia) or gain-of-function (e.g., paroxysmal extreme pain disorder) pain phenotypes. We exploited existing technologies in a novel manner to identify selective antagonists of NaV 1.7. A full-deck high-throughput screen was developed for both NaV 1.7 and cardiac NaV 1.5 channels using a cell-based membrane potential dye FLIPR assay. In assay development, known local anesthetic site inhibitors produced a decrease in maximal response; however, a subset of compounds exhibited a concentration-dependent delay in the onset of the response with little change in the peak of the response at any concentration. Therefore, two methods of analysis were employed for the screen: one to measure peak response and another to measure area under the curve, which would capture the delay-to-onset phenotype. Although a number of compounds were identified by a selective reduction in peak response in NaV 1.7 relative to 1.5, the AUC measurement and a subsequent refinement of this measurement were able to differentiate compounds with NaV 1.7 pharmacological selectivity over NaV 1.5 as confirmed in electrophysiology.